2021
DOI: 10.1111/jcmm.16594
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptome analysis of human oocyte ageing

Abstract: Oocyte ageing is a key bottleneck and intractable challenge for in vitro fertilization treatment of aged female patients. The underlying molecular mechanisms of human oocyte ageing remain to be elucidated. Hence, this study aims to investigate the key genes and relevant biological signalling pathways involved in human oocyte ageing. We isolated mRNA for single‐cell RNA sequencing from MII human oocytes donated by patients undergoing intracytoplasmic sperm injection. Nine RNA‐seq datasets were analyzed, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
(49 reference statements)
0
26
0
Order By: Relevance
“…All patients received standard antagonist protocol for ovarian stimulation [ 90 ]. Patients were injected with recombinant FSH (Gonal-F, Merck, Italy) on day 2 of their menstrual cycle with a starting dose of 150 IU/d.…”
Section: Methodsmentioning
confidence: 99%
“…All patients received standard antagonist protocol for ovarian stimulation [ 90 ]. Patients were injected with recombinant FSH (Gonal-F, Merck, Italy) on day 2 of their menstrual cycle with a starting dose of 150 IU/d.…”
Section: Methodsmentioning
confidence: 99%
“…To build cell-cell interactions between somatic cells and oocytes in young and old human ovaries, we used CellChat 45 (v1.1.3) to infer the cell-cell interactions based on the expression of known ligand-receptor pairs in different cell types with a combination of our snRNA-seq datasets and publicly available human oocyte single-cell RNA-seq datasets 46 from reproductive young and old females. Briefly, we inferred the cell-cell interactions for young and old ovaries, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To explore potential age-related alterations to the ovarian cellular communication network, we used CellChat 45 , which models the probability of the cell-cell interaction network based on gene expression and prior knowledge of ligand-receptor interactions. To gain insight into the intercellular communication between ovarian somatic cells and oocytes, we integrated our snRNA-seq with publicly available human oocyte single-cell transcriptomes from young and reproductively aged ovaries 46 . We found that ageing slightly reduced both the total number and overall strength of intercellular interactions (Supplementary Fig.…”
Section: Mainmentioning
confidence: 99%
“…Different analysis methods were used in each study, and the results of these studies remain controversial. Some studies reported that gene expression data for the human germinal vesicle (GV) oocytes [ 11 , 12 ], from women across age groups, remained stable; while others revealed that gene expression among GV oocytes [ 13 ], in vivo ovulation-metaphase Ⅱ (IVO-MII) oocytes [ 14 , 15 , 16 , 17 ], and in vitro maturation-metaphase II (IVM-MII) oocytes [ 12 , 13 ], were significantly influenced by maternal age. To obtain more generalizable results, multi-center studies with large sample sizes are required.…”
Section: Introductionmentioning
confidence: 99%